Pengaruh Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Pegawai pada Inspektorat Daerah Provinsi Kalimantan Timur (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine how much the work environment and discipline affect employee performance at the Inspectorate of East Kalimantan Province. A quantitative approach was used in this study, and 86 observations and respondent questionnaires were used to collect data. Using the SPSS application, a multiple linear regression approach was used to analyze the data. The findings of this study indicate that employee performance is positively and significantly influenced by the work environment and work discipline, both independently and in combination. Punctuality, productivity, and quality of work output are all influenced by work discipline. Meanwhile, a friendly workplace can foster comfort and improve relationships between employees. These results emphasize the importance of implementing discipline consistently and the importance of building a positive work atmosphere to improve employee performance. This study contributes significantly to the HRM initiatives of government institutions, especially those aimed at improving the efficacy and efficiency of worker productivity.